Federal incentives for community-level climate adaptation: an evaluation of FEMA's Community Rating System. (2nd March 2023) - Gourevitch, Jesse D; Pinter, Nicholas
Abstract: In response to growing threats of climate change, the US federal government is increasingly supporting community-level investments in resilience to natural hazards. As such federal programs become more widespread, evaluating their efficiency and equity is essential. The Community Rating System (CRS), which is part of the National Flood Insurance Program (NFIP), is a promising example of a federal policy designed to reduce flood losses by providing financial incentives for local climate adaptation. In exchange for community engagement in a range of risk communication and risk reduction activities, CRS provides discounts on NFIP premiums ranging from 5% to 45%. Using national-scale NFIP claims, policies, and CRS data between 1998 and 2020, we assess the program, asking whether it has been effective in reducing flood losses, how it can be improved, and what lessons it holds for similar programs. We find that participation in CRS is associated with reduced flood damage, with the percent reduction in claims roughly proportional to NFIP premium discounts. Among CRS activities, those related to 'Flood Damage Reduction' are most effective in reducing flood losses and are associated with a 20%–30% decrease in NFIP claims. Between 1998 and 2020, cumulative damage reductions attributable to CRS were $11.4 billion; over the same period, cumulative NFIP premium discounts were $12.1 billion. This close match is an endorsement of CRS historically and supports its future continuation. To improve the efficiency and equity of CRS, we recommend that Federal Emergency Management Agency: (a) reexamine the surcharge levied on NFIP premiums that cross-subsidizes premium discounts, and (b) allocate greater resources towards supporting participation among smaller, under-resourced communities. In general, CRS serves as an effective model for other federal market-based programs seeking to stimulate community-level investment in climate resilience.